2013
DOI: 10.22146/ijc.21322
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gamma Irradiation on Mechanical and Thermal Properties of Fish Gelatin Film Isolated from <i>Lates Calcarifer</i> Scales

Abstract: The objective of this research was to investigate the effect of gamma irradiation on mechanical and thermal properties of fish gelatin films prepared from scales of Lates calcarifer. The films were irradiated by gamma rays at varied doses (0-50 kGy). The mechanical and thermal properties of irradiated gelatin films were measured by using colorimeter, Universal Testing Machine, Differential Scanning Calorimetry (DSC), and Fourier Transform Infrared (FTIR) spectrophotometer. The results showed that increasing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…It is worth mentioning that contrary to the highenergy gamma radiation, like ionizing radiation, which might compromise their potential applications for proteinbased films, UVRT is safe to use even in edible films due to its low energy (Otoni et al, 2012). Moreover, Perkasa et al (2013) also correlated the crosslinking density of fish skin gelatin with the treatment time of UVRT. Short-time UVRT led to intermolecular crosslinking of gelatin, while longtime UVRT acted on the breakage of gelatin molecular chains.…”
Section: Nonthermal Technical Methodsmentioning
confidence: 98%
“…It is worth mentioning that contrary to the highenergy gamma radiation, like ionizing radiation, which might compromise their potential applications for proteinbased films, UVRT is safe to use even in edible films due to its low energy (Otoni et al, 2012). Moreover, Perkasa et al (2013) also correlated the crosslinking density of fish skin gelatin with the treatment time of UVRT. Short-time UVRT led to intermolecular crosslinking of gelatin, while longtime UVRT acted on the breakage of gelatin molecular chains.…”
Section: Nonthermal Technical Methodsmentioning
confidence: 98%
“…Notably, a new functional imine group (HC=N) was discovered in the band of 1610–1621 cm −1 for the sterilized HyS-w/γ macrospheres. [ 53 , 54 ] A study indicated that the amide group may decompose and transform into a new imine or nitrile group after irradiation [ 55 ]. Accordingly, the possible mechanisms of amide decomposition into more active imine or nitrile groups are displayed in Figure 3 b.…”
Section: Resultsmentioning
confidence: 99%
“…They found a slight improvement of the tensile strength at an irradiation dose of 100 kGy, maybe due to the cross‐linking of proteins chains by irradiation, but without any confirmation from other complementarily analyses. Recently, Perkasa and others () also noticed an increase of the tensile strength after cross‐linking of solid and dried fish gelatin films using electron beam irradiation at a 50 kGy dose. Likewise, Benbettaïeb and others () worked on the effect of electron beam irradiation dose at 60 kGy on the functional properties of chitosan–gelatin blend films.…”
Section: Introductionmentioning
confidence: 94%